Engineering technology is a necessity to meet industrial needs - UMP, PNC
Universiti Malaysia Pahang (UMP)’s Faculty of Technology organised a Public Lecture on Engineering Technology at Royale Bintang Hotel in Kuala Lumpur on May 15, 2013.